Harmonization of Islam and human rights: judges’ legal arguments in rejecting child marriage dispensation in Sukadana, Indonesia - M Anwar Nawawi; Sulastri Sulastri; Relit Nur Edi; Agus Setiawan (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
This article analyzes the rejection of an application for child marriage dispensation at the Sukadana Religious Court, Indonesia. Normatively, building a family and preserving the lineage are human rights, but the judges reject the application for the marriage dispensation. This normative research used observation, interviews, and documentation to collect data. In rejecting the marriage dispensation, the Religious Court judges used two arguments: normative (fiqh rules) and juridical (regulations related to human rights). The legal arguments integrate Islamic values (benefits and avoiding disgrace) with human rights principles. They seek to protect the petitioners' human rights, especially children's rights. From the finding above, the researchers suggest that there is no conflict between Islam and human rights. Both harmonize in their value of protecting the citizens. This study has implications for the increased unregistered marriages that do not have legality.